Use of Plant Derived Ash as Potassium Fertilizer and Its Effects on Soil Nutrient Status and Cocoa Growth - John Bako Baon (UNIVERSITY OF LAMPUNG, 2009)
Analternative to replacing the expensive potassium (K) fertilizers, such as KCl, should be investigated by Indonesia as the third largest cocoa (Theobroma cacao L.) producing country. The objective of this study is to investigate the effect of plant derived ash (PDAsh) application on soil nutrient status and growth of cocoa. This research was conducted in ICCRI, Jember, using a soil from Balung subdistrict, Jember, East Java. Two series of experiments with and without cocoa plants consisted of six treatments replicated four times were laid in randomized completly block design. The six treatments of K2O applied were 0, 300, 600, 900, 1200 and 1500 mg 2.5 kg-1 soil. Results of this study showed that application of PDAsh as K fertilizer increased the availability of K and Mg in soil and K content in plant tissue. In case of Mn, the concentration in soil decreased in the experiment with cocoa plants, on the other hand the concentration increased where no cocoa plants and the relation followed quadratic curve. The results also indicated that application of PDAsh up to 1500 mg K2O 2.5 kg-1soil resulted in soil pH of 7.4 in two months after application and reached 6.8 in 6 months compared with the pH of ash was 13. Application of PDAsh 700 mg 2.5 kg-1soil resulted in optimum cocoa seedling growth compared to other dosages tested, in term of plant height, plant diameter, leaf number, fresh and dry shoot weight.